Forensic tactics: a review of the formation history and current trends - O. P. Shaituro (Bulletin of Kharkiv National University of Internal Affairs)
A review of domestic and foreign scholars’ research on the formation and development history of forensic tactics has been made: from ancient times to the latest trends of the XXI century. The existing in the scientific literature approaches to the periodization of the development of forensic tactics are given, the most important works of researchers are noted, the publication of which is associated with new stages of forensic tactics development.